2012
DOI: 10.1073/pnas.1113632109
|View full text |Cite
|
Sign up to set email alerts
|

Growth-induced hormone dilution can explain the dynamics of plant root cell elongation

Abstract: In the elongation zone of the Arabidopsis thaliana plant root, cells undergo rapid elongation, increasing their length by ∼10-fold over 5 h while maintaining a constant radius. Although progress is being made in understanding how this growth is regulated, little consideration has been given as to how cell elongation affects the distribution of the key regulating hormones. Using a multiscale mathematical model and measurements of growth dynamics, we investigate the distribution of the hormone gibberellin in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
125
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(134 citation statements)
references
References 40 publications
7
125
2
Order By: Relevance
“…A recent analysis in this vein was performed on gibberellin perception in [86]. The authors embedded the model developed in [78] in a multi-scale spatial framework to analyse the interplay between GA signalling and root growth.…”
Section: Multi-scale Analysis Of Plant Signallingmentioning
confidence: 99%
“…A recent analysis in this vein was performed on gibberellin perception in [86]. The authors embedded the model developed in [78] in a multi-scale spatial framework to analyse the interplay between GA signalling and root growth.…”
Section: Multi-scale Analysis Of Plant Signallingmentioning
confidence: 99%
“…Spatial gradients in growth hormones (auxin and GA) were proposed (Went and Thimann, 1937;Sánchez-Bravo et al, 1992;Band et al, 2012), but hormones are several steps removed from the biochemical and biophysical processes that drive cell growth (e.g. cell wall loosening and stress relaxation, leading to water uptake and concomitant expansion of the cell wall; Cosgrove, 2016).…”
mentioning
confidence: 99%
“…The combination of experimental and modelling analysis enables the study of plant hormone gradients as an integrated system, in which the causal relationships of all components can be established. To date, this approach has led to an improved understanding of, for example, how PIN proteins play a key role in auxin patterning and root growth (Grieneisen et al, 2007); how asymmetric auxin gradients link to gravitropsim (Band et al 2012; see also doi: 10.1002/9780470015902.a0025267);…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that growth-induced hormone dilution can explain the dynamics of plant root cell elongation (Band et al, 2012).…”
Section: B Interaction Of Growth and Hormone Gradientsmentioning
confidence: 99%